30th AIAA Aerodynamic Measurement Technology and Ground Testing Conference 2014
DOI: 10.2514/6.2014-2652
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the NASA Langley Arc Heated Scramjet Test Facility using NO PLIF

Abstract: The nitric oxide planar laser-induced fluorescence (NO PLIF) imaging was used to characterize the air flow of the NASA Langley Arc Heated Scramjet Test Facility (AHSTF) configured with a Mach 6 nozzle. The arc raises the enthalpy of the test gas in AHSTF, producing nitric oxide. Nitric oxide persists as the temperature drops through the nozzle into the test section. NO PLIF was used to qualitatively visualize the flowfield at different experimental conditions, measure the temperature of the gas flow exiting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Prior to conducting mixing tests, earlier experiments were conducted in the AHSTF with the laser sheet configured to interrogate the flow at the exit of the Mach 6 facility nozzle. 18 These tests confirmed that NO exists in sufficient concentration (i.e., to produce enough fluorescence to detect) and sufficient spatial uniformity for images obtained from the mixing flowfield to be interpreted properly (i.e., concentration of NO proportional to concentration of air). The initial set of mixing tests of the injectors described above has been conducted using only NO PLIF imaging and no intrusive measurements.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…Prior to conducting mixing tests, earlier experiments were conducted in the AHSTF with the laser sheet configured to interrogate the flow at the exit of the Mach 6 facility nozzle. 18 These tests confirmed that NO exists in sufficient concentration (i.e., to produce enough fluorescence to detect) and sufficient spatial uniformity for images obtained from the mixing flowfield to be interpreted properly (i.e., concentration of NO proportional to concentration of air). The initial set of mixing tests of the injectors described above has been conducted using only NO PLIF imaging and no intrusive measurements.…”
Section: Introductionmentioning
confidence: 61%
“…Figures [16][17][18][19][20] show the comparisons between the time-averaged PLIF images and the corresponding computationally derived PLIF, termed CFI, obtained for different fuel injectors and using different sets of LIF transition lines. Figure 16 shows the time-averaged streamwise images obtained along the centerline of the strut injector block and cutting through the middle injector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adequate testing for these types of conditions is a challenge in and of itself. Current test facilities [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] consist of combustion, arc-plasma, laser or combinations thereof to generate the temperatures, velocities and/or environments of interest (Table 1). Most of these rigs can effectively evaluate two or, at most, three of the above conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Related to this is the need for diagnostic techniques to measure thermal gradients and local strain as well as health-monitoring techniques to assess the progressive damage that occurs during the test. [3] Jet fuel combustion 0.1 1550 AFIT HVOF [4] Combustion 1 2500 HYMETS [5][6][7] Arc-plasma 5 2480 NASA Combustion Scramjet * [8] Combustion Scramjet 6 1400 NASA Arc-Heated Scramjet * [9][10][11] Arc-heated Scramjet 8 2600 GHIBLI [12] Arc-plasma 10 9700 SCIROCCO * [13][14][15][16] Arc-plasma 12 9700 Pprime MAATRE * [17] Burner Rig 1 1600 VKI Plasmatron * [18] and other plasma [19][20][21] Induction-Plasma 1 11,700 DRL HEG* [22,23] Free-Piston Shock Tunnel 10 1176 * Capable of large specimen size (>250 mm).…”
Section: Introductionmentioning
confidence: 99%